Modeling Reinforced Concrete Column with GRFP Transverse Reinforcement - Adena, Haura; Alrasyid, Harun; Sutrisno, Wahyuniarsih; Piscesa, Bambang (Institut Teknologi Sepuluh Nopember, 2025)
The utilization of GFRP (Glass Fiber Reinforced Polymer) in reinforced concrete structures is gaining attention due to its high strength and low corrosion. The application of GRFP rebar as longitudinal and tranverse reinforced columns has been studied through experimental testing. However it is important to understand the deformation responses and to predict the behavior of concrete columns with GRFP Rebar. This objective requires suitable and effective tools. This study presents Finite Element Analysis of Concrete Column reinforced with GRFP Rebar using 3DNLFEA. The result showed that The analysis result exhibited that the prediction of model behavior corresponds well with the experimental results.